Perlindungan Hukum Modifikasi Game Pihak Ketiga Studi Kasus GTA San Andreas Indonesia Hak Cipta - Kristoforus Pedro Naibaho; Adhitya Widya Kartika (Journal Kompilasi Hukum, 2026)
The proliferation of user-generated game modifications in Indonesia, exemplified by the GTA San Andreas Indonesia project, has created significant legal tension between grassroots digital creativity and the exclusive rights of copyright holders. This local modification transforms the original Grand Theft Auto: San Andreas by injecting Indonesian socio-cultural elements, yet it operates without formal authorisation from the rights holder, Rockstar Games, thereby raising fundamental questions about the boundaries of derivative works under Indonesian law. This study aims to analyse the legal status of third-party game modifications within the framework of Law No. 28 of 2014 on Copyright and to examine the forms of legal liability arising from potential violations of the original creator’s moral and economic rights, as well as the contradictions inherent in End User License Agreements (EULA). Employing a normative juridical method, this research utilises statutory and conceptual approaches to critically evaluate the applicable legal norms against the realities of digital innovation. The findings reveal that, from a positivist legal standpoint, the GTA San Andreas Indonesia modification constitutes an unlawful derivative work due to the absence of written consent from the copyright owner, as mandated by Article 9 of the Copyright Law. Furthermore, the circumvention of technological protection measures through reverse engineering techniques explicitly violates Article 52 of the same law. The analysis further indicates that while such modifications formally infringe upon the creator’s moral and economic rights, the selective tolerance exhibited by developers operates merely as a strategy of “tolerated infringement”, thereby creating profound legal uncertainty. The study concludes that the current legal framework fails to accommodate the transformative socio-cultural value of non-commercial modding, underscoring an urgent need for regulatory reform to establish fair use parameters and balance exclusive rights with public innovation.